Genetic improvement of iron toxicity tolerance in rice-progress, challenges and prospects in West Africa - Sikirou, M.; Saito, Kazuki; Achigan-Dako, Enoch G.; Drame, K.N.; Ahanchédé, A.; Venuprasad, R. (Informa UK Limited, 2015)
In sub-Saharan Africa, the demand for higher rice production continues to grow rapidly. Although there is a huge potential for increasing rice production through expansion of the rice cultivation area in wetlands, iron (Fe) toxicity tends to occur and consequently results in low rice yield. Development and deployment of varieties tolerant to Fe toxicity is one of the practical options to overcome this constraint. Several tolerant varieties have been developed through conventional breeding but progress in breeding has been generally slow mainly due to large genotype × environment interaction and field heterogeneity, which make rice selection ineffective. In addition, there are no valid managed-stress screening protocols which are highly efficient and that can predict rice performance in the diverse target environments of West Africa. Many O. glaberrima accessions have superior tolerance, but only a few of them have been utilized in breeding programs. The known quantitative trait loci (QTLs) related to Fe toxicity, have not been used for marker-assisted selection (MAS), as they gave small effects with a large confidence interval. Accelerating rice breeding efficiency for tolerance to Fe toxicity requires establishment of reliable screening protocols, use of O. glaberrima accessions as donors, identification of large-effect QTLs and MAS using such QTLs. This paper reviews the past and current efforts in West Africa to develop new varieties with superior tolerance to Fe toxicity.